The end of the world is just the beginning : mapping the collapse of globalization - Zeihan, Peter (Harper Business, an imprint of HarperCollinsPublishers, 2022)
"As isolationism and realism become the dominant values of a previously interconnected world, the logic that motivated international relations and global trade must be reevaluated. Zeihan uses a mixture of geographical knowledge, political history, and sharp analysis to predict the shape of the next twenty years on the world stage"--